ANALISA POSITIONING SUPERMARKET (LOTTEMART,SUPERINDO,TIPTOP,CARREFOUR,GIANT) BERDASARKAN ATRIBUT YANG DIPERSEPSIKAN OLEH KONSUMEN - SUHA RINI RINI (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Of course everyone has different experiences and perceptions in terms of shopping at the supermarket, and it can be used as a tool to find out how consumers' assessment of the attributes of the supermarket which include: location, products, services salesperson, cashier, the price of goods, discount, direct gifts, cleanliness, air conditioning, free parking. After knowing what consumers' assessment of their attributes can be further analyzed how the "positioning" Supermarket, in here researcher interested to explore five supermarkets in the district Ciputat,namely LotteMart, SUPERINDO, TIPTOP, CARREFOUR and GIANT.Research carried out by taking as many as 31 respondents who shopped at supermarkets above mentioned. Responden asked to choose the answer satisfied or not satisfied with the list of 11 statements related to the attributes mentioned above.Based on data obtained through structured interviews, and analyzed using methods Correspondence Analysis it could be concluded that the LOTTE MART and SUPERINDO are Sepermarket capable of satisfying the consumer in terms of "location" and "free parking". TIPTOP able to satisfy consumers in terms of "price," "discount" and "instant prize" CARREFOUR satisfying consumers with "Hygiene" and The rooms were very cool with "air conditioning". GIANT has managed to satisfy consumers in terms of "product", "service salesperson ", and" cashier ". That positioning of five supermarkets in the District Ciputat based on consumer perception.Keywords:positioning,supermarket,perception,consumers